2005
DOI: 10.1073/pnas.0503826102
|View full text |Cite
|
Sign up to set email alerts
|

Induced conformational changes upon Cd 2+ binding at photosynthetic reaction centers

Abstract: Cd 2؉ binding at the bacterial photosynthetic reaction center (bRC) from Rhodobacter sphaeroides is known to inhibit proton transfer (PT) from bulk solvent to the secondary quinone Q B. To elucidate this mechanism, we calculated the pK a for residues along the water channels connecting Q B with the stromal side based on the crystal structures of WT-bRC and Cd 2؉ -bound bRC. Upon Cd 2؉ binding, we observed the release of two protons from His-H126͞128 at the Cd 2؉ binding site and significant pKa shifts for resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 47 publications
(124 reference statements)
0
32
0
Order By: Relevance
“…As described in previous applications (2,28,29), hydrogen atom positions were energetically optimized with CHARMM (30), keeping the positions of all nonhydrogen atoms fixed at crystallographically determined coordinates while all titratable groups were in their standard protonation states [i.e., acidic groups ionized and basic groups (including titratable histidines) protonated]. His residues that are ligands of Chla were treated as nontitratable with neutral charge.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…As described in previous applications (2,28,29), hydrogen atom positions were energetically optimized with CHARMM (30), keeping the positions of all nonhydrogen atoms fixed at crystallographically determined coordinates while all titratable groups were in their standard protonation states [i.e., acidic groups ionized and basic groups (including titratable histidines) protonated]. His residues that are ligands of Chla were treated as nontitratable with neutral charge.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…The aim of the present experiments was to test the effect of selenium on the activity of the photosynthesis under stress conditions generated by Cd. Numerous data point to the interference of cadmium with the functioning of chloroplasts, especially its interaction with redox-active components of the PS2 system, as, e.g., with the quinone-iron complex (Q A -Fe-Q B ) on the PS2 side (Ishikita and Knapp 2005). It was shown that Cd inhibited the electron transfer between Q A and Q B probably via changing the protonation states of the histidine residues in the vicinity of Q B state (Paddock et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…These intriguing observations prompted us to investigate in detail NHFe in Rs. rubrum, in particular, how its low spin state is affected by fluctuations of protein matrix and by Cd 2+ ions, which are known to bind in the vicinity of the iron-quinone complex [22,23]. To this end, Mössbauer spectroscopy was applied to compare the valence and spin states of Fe atoms in native RC from Rs.…”
mentioning
confidence: 99%